Desenvolvimento de aglomerante hidráulico por tratamento termomecânico de produtos da hidratação de pasta de cimento Portland e da ativação de agregado miúdo silicoso - Raquel Maria Rocha Oliveira Menezes (2018)
The recycling of ceramic materials present in construction waste and construction and demolition waste is a worldwide practice for the the production of cement compounds with lower environmental impact. Commonly, such wastes are crushed and used as aggregates for the manufacture of concrete, most often without structural purposes. Studies of the literature indicate that it is possible to recover and reuse the large aggregates present in the residues. However, there is practically no data on the recovery of cement and quartzous aggregate (sand). With the objective of contributing to the recovery of these materials, this work studies the decomposition of the cement hydration products, in order to recover it by thermal and mechanical treatment. The functionalization of the small aggregate is also evaluated through mechanical activation. For this, residues generated in the laboratory, from Portland cement pastes, were submitted to thermomechanical treatment, aiming to recover the cement by dehydration. In parallel, mechanical activation of natural silica sand was carried out in order to favor its reactivity with calcium hydroxide. The results confirm that it is possible to remove the water responsible for the hydration of the compounds of the Portland cement employed at temperatures around 550 °C and indicate that their use associated with sand dust (37m²/g)generates a binder with characteristics similar to those of in natura cement, an alternative cementitious supplement/binder material. An analysis of the equivalent energy consumption allows to estimate that the electrical energy required for the decomposition of the paste by thermomechanical treatment and the consumption of carbon equivalent are significantly lower than those associated with the production of Portland cement.